Who works in agriculture?: exploring the dynamics of youth involvement in the agri-food systems of Tanzania and Malawi - Kafle, Kashi; Paliwal, N.; Benfica, Rui (International Fund for Agricultural Development, 2019)
This analysis examines the dynamics of employment in agriculture and the agri-food system in Tanzania and Malawi by assessing the population age structure and movements of youth (aged 15-24) and young adults (aged 25-34) in and out of agriculture and the agri-food system. Using internationally comparable integrated household and agriculture surveys, we discover that the average age of a person who works in farming as own-farm labour is 34 years in Tanzania and 31 years in Malawi. Examination of the movements into and out of the agri-food system demonstrates a high degree of short-term stability of youth and young adult participation in farming in both countries. Specifically, 59 per cent of rural Tanzanian youth and 56 per cent of rural Malawian youth are consistently engaged in farming. Yet there is considerable mobility between different sectors of employment. More than 57 per cent of the youth cohort that was not involved in the agri-food system during the baseline entered the sector in the subsequent wave, and 12 per cent of those involved in the agri-food system during the baseline moved out of the sector in the subsequent wave. Even though the high degree of stability in farming participation is encouraging, it is likely that the poor economic prospects outside farming are what is driving strong participation in single-occupation farming. Given that increasing youth employment is a priority public policy for the Governments of Tanzania and Malawi, it is recommended that the countries attempt to diversify the rural economy by developing the many economic opportunities within the agri-food system.